Informational Boundaries of the State - Thiemo Fetzer; Callum Shaw; Jacob Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2024)
Formal conceptions of state capacity have mostly focused on indirect measures of state capacity – by, for instance, using the state's fiscal or extractive capacity as a proxy for its overall capacity. Yet, this input or extractive view of state capacity falls short, especially since cross-country empirical evidence suggests that similar levels of fiscal capacity, measured by tax revenues as a percentage of GDP, can produce starkly different outputs – both in classic economic terms and in broader terms that citizens would recognize as desirable outcomes, including quality of life, health, security, equality of opportunity, and intergenerational mobility. This paper argues that a central step towards addressing these shortcomings of the conventional view is to account for a crucial and largely ignored boundary of the state or dimension of state capacity: its capacity to gather, process, and deploy information in its conduct of fiscal policy. Specifically, we study how the presence or lack of such informational capacity constrains governments in responding to crises, such as the recent energy price shock. Our framework provides the analytical toolkit to examine how the informational boundary of the state shapes the incentives for policymakers to resort to untargeted and/or distortionary policy instruments, as opposed to targeted and non-distortionary ones, in responding to crises. The policy response to the energy crisis following the invasion of Ukraine provides the empirical context upon which we bring this theoretical framework to bear on data, though the latter can be straightforwardly extended to other recent crises.
Keywords: H11; O43; D63; D73; Q48; P16; C21; C55; 330; state capacity; economic development; carbon taxation; political economy; pork-barrel politics